1999
DOI: 10.1074/jbc.274.36.25945
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-Protein Fibrillogenesis

Abstract: Alzheimer's disease is characterized by extensive cerebral amyloid deposition. Amyloid deposits associated with damaged neuropil and blood vessels contain abundant fibrils formed by the amyloid ␤-protein (A␤). Fibrils, both in vitro and in vivo, are neurotoxic. For this reason, substantial effort has been expended to develop therapeutic approaches to control A␤ production and amyloidogenesis. Achievement of the latter goal is facilitated by a rigorous mechanistic understanding of the fibrillogenesis process. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
460
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 999 publications
(504 citation statements)
references
References 66 publications
42
460
2
Order By: Relevance
“…The percentage of ordered residues in aqueous A␤ 39 in our simulations agrees reasonably with the NMR data 35,36 that estimate the amount of disordered structure to be 60%-80%, and ␣ helices to be 10%. However, our simulations did not reveal the origin of the 25% ␤ content found in CD studies for disordered A␤ 39 in water.…”
Section: -3supporting
confidence: 78%
See 1 more Smart Citation
“…The percentage of ordered residues in aqueous A␤ 39 in our simulations agrees reasonably with the NMR data 35,36 that estimate the amount of disordered structure to be 60%-80%, and ␣ helices to be 10%. However, our simulations did not reveal the origin of the 25% ␤ content found in CD studies for disordered A␤ 39 in water.…”
Section: -3supporting
confidence: 78%
“…Ma and Nussinov 11 suggested that at high temperature fragments A␤ [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and A␤ form a strand-loop-strand structure with parallel ␤ sheet, with an interior salt bridge between Asp23 and Lys28 residues as a major element of the fibril structure. On the other hand, computational studies using coarse-grained as well as atomistic atom models suggest the formation of antiparallel ␤ sheets by A␤ [16][17][18][19][20][21][22] subpeptides.…”
Section: Introductionmentioning
confidence: 99%
“…P rotofibrils and oligomers are metastable peptide assemblies observed during the growth of amyloid fibrils by a number of peptides, including the Alzheimer's amyloid plaque peptide A␤ (1)(2)(3). These oligomeric assemblies are important for at least two reasons.…”
mentioning
confidence: 99%
“…First, it is now believed that such forms, rather than mature fibrils, may be the cytotoxic agents responsible for some amyloid-associated disorders like Alzheimer's and Parkinson's diseases (4,5). Second, it has been postulated that these structures may be intimately involved in the amyloid fibril assembly mechanism, both in amyloid nucleation and fibril elongation (2,3,6).…”
mentioning
confidence: 99%
“…Recent findings suggest that brains of individuals with AD also contain soluble and neurotoxic A␤ oligomers, which seem to be an intermediate state in the A␤-aggregation cascade, whose downstream product is the senile plaque (3)(4)(5)(6)(7)(8)(9)(10). There is poor correlation between the severity of dementia and the density of amyloid plaques in AD (11)(12)(13); furthermore, in mice transgenic for the human A␤ precursor protein (APP), synaptic degeneration and cognitive decline are observed even before amyloid is deposited (14)(15)(16).…”
mentioning
confidence: 99%